The Predicted Distribution of Javan Munia (Lonchura leucogastroides) in Indonesia based of Behavior Analysis in Kalibaru, Banyuwangi, East Java - Kurnianto, Agung Sih; Kurniawan, Nia (Biotropika: Journal of Tropical Biology, 2013)
Javan Munia is one of the common species of birds that found in west area of Indonesia (Sunda land). This species is endemic to Indonesia (Lombok, Bali, Java, and South Sumatra). The large population, especially during the harvest season makes this bird became a major pest for agriculture. This research aims to determine the adaptive behaviors of Javan Munia that become major reasons of widely spreads and the influence of these factors to the distribution. Observations made in Kalibaru, Banyuwangi, East Java, which is a mostly agricultural area. Any form of behavior in the territorial area (nesting and courtship areas) and range area (where colonize and feed) were observed periodically in the past 12 months. Sunbathing is known as a activity that undertaken by many species of birds, including the Javan Munia. This munia has specific mating and nest construction behaviour. The development of Javan Munia is very quickly, in 40 days, child will become a new adult. Javan Munia is very easy to adapt to the surrounding environment, including the used of oil palm (Elais guineensis) fiber and paper receipts as nest material. There are a possibility of invasive occurrence to the entire island of Sumatra by this species. It is quite possible because of the opening of oil palm plantations and settlements continue, until Aceh. The spread possibilty to east end of distribution (Lombok) can occur up to Nusa Tenggara Island, because of short distances between the islands and similiar vegetation circumstances.